Evolution оf the European Energy Policy - Boneva, Svetla (Research Papers, 2018)
The main objective of the research is to present the development of the European Union (EU) energy policy for the period 1951- 2017. It represents an analysis of the main strategic documents and regulatory framework shaping the contemporary EU energy policy.The research methods used in the study involve elements of retrospective analysis and content analysis. This is a conceptual study and a posteriori research approach has been followed for its development. The thesis of the research is that in the contemporary conditions of deepening integration between the European Union member states in the energy sector, the clear formulation and strict implementation of the components of the energy policy by all EU member states is of key importance for the construction of a real and functioning European Energy Union. The main results of the research represent generalizations, systematizations and analyses of the basic elements of future common energy policy and the dimensions of the European Energy Union. The results of the research provide ground for evidence-based recommendations and decisions on the future policy measures in the energy sector and their implementation in the EU member states.The conclusion of the research is that the idea of the European Commission for a common approach to the EU energy policy has been shared by the EU member states. The EU member states have to work together for the implementation of a macro-regional energy union. Future developments will outline the outcomes of the European Energy Union depending on the willingness of the EU member states to transfer competences in the energy field to the European Union.